High-fat diet combined with low-dose streptozotocin injections induces metabolic syndrome in Macaca mulatta - Li, L.; Liao, G.; Yang, G.; Lu, Y.; Du, X.; Liu, J.; Li, L.; Wang, C.; Li, L.; Ren, Y.; Zhong, Z.; Cheng, J.; et al. (2015)
Metabolic syndrome (MetS) is associated with abdominal obesity, hyperlipidemia, insulin resistance, and type 2 diabetes mellitus, and increases the risk of cardiovascular disease. Given the complex multifactorial pathogenesis of MetS, qualified animal models are currently seriously limited for researchers. The aim of our study was to develop a MetS model in juvenile rhesus monkeys (Macaca mulatta). Rhesus monkeys (1-year-old) fed a high-fat diet (15 % fat, 2 % cholesterol) were used as the HF group (n = 6), and those on a normal diet (5 % fat) were used as the control group (n = 4). After being fed a high-fat diet for approximately 12 months, 2 monkeys (HF + STZ group) were injected with low-dose streptozotocin (STZ, 25 mg/kg) twice, with a 7 days interval, and were then fed the same diet continuously for another 24 months. After 36 months of treatment, the high-fat diet monkeys, including the HF and HF + STZ groups, had acquired increased body weights, abnormal serum lipids, and impaired glucose tolerance compared to the control group. In addition, much more marked metabolic changes were observed in the two monkeys of the HF + STZ group, particularly in terms of high-blood glucose level and insulin resistance. Morphological observation of biopsies of liver and pancreatic tissues showed decreased islet number and mass and decreased insulin staining in the monkeys of the HF + STZ group. In addition, Oil red O staining suggested remarkable accumulation of lipid droplets in the hepatocytes. Our study suggested that a long-term high-fat diet followed with a low-dose STZ was able to induce MetS in juvenile rhesus monkeys with faster pathophysiological progress compared with high-fat diet induction alone. Our primary data showed that this method may have potentials to develop MetS animal model in non-human primates.